The principle of a social state - Korpič - Horvat, Etelka (Anali PAZU HD, 2022)
The principle of a social state is one of the fundamental principles determined in Article 2 of the Constitution of the Republic of Slovenia. Its implementation affects all areas of life. Individuals expect from a social state to provide a basis for a dignified life regardless of age and their position either as children, pupils, students, workers, unemployed, parents, elderly, etc. In the article the author outlines through the analysis of the individual decisions of the Constitutional Court of the Republic of Slovenia in what manner the Constitutional Court gives substance to the principle of a social state. As a guardian of constitutionality, legality, human rights and fundamental freedoms the Constitutional Court importantly shapes the standards of the social rights protection. Through this perspective the author also discusses the role of the state in preservation and development of such rights.
Keywords: the state; a social state; a principle; human rights; dignity